ANALYSIS OF CHILDREN POETRY WRITING SKILLS ON CLASS V STUDENTS SDN 181 PEKANBARU - Ghea Febian Huda (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine the poetry writing skills of students in class V SDN 181 Pekanbaru based on aspects of theme, imagination, diction, and performance. Because of the lack of students 'poetry writing skills due to students' lack of skill in expressing ideas and thoughts. therefore by analyzing we can find out which aspects are not mastered by students. The study was conducted in class V odd semester of 2019. The sample in this study was saturated sampling. The assessment instrument used was a poetry writing skills test using a poetry writing assessment descriptor. The data obtained from poetry writing skills seen from 4 aspects, namely theme, imagination, diction and presentation, it can be concluded that the poetry writing skills of children who are categorized as highly skilled there are 5 (3.67%), then 9 (6.57%) skilled categories , and 103 (75.18%) were categorized as quite skilled, while students who were categorized as less skilled were 20 (14.60%) as a whole. Over all poetry writing skills class V SND 181 Pekanbaru obtain the average value of 64 categorized enough